Preparation, characterization and turbidity removal of kaolin suspension of polyacrylamide grafted chicken egg white / Nor Fateha Azuan - Azuan, Nor Fateha (2021)
The polyacrylamide grafted chicken egg white (Egg-g-PAM) has been successfully synthesized by microwave-assisted graft copolymerization technique using ceric ammonium nitrate (CAN) as an initiator. This study aims to optimize the percentage of grafting efficiency (%GE) of Egg-g-PAM at various parameters (acrylamide (AM) weight, CAN weight and microwave irradiation time) and characterization by the percentage of water absorption (%WA), CHN elemental analysis, Fourier transform infrared (FTIR) spectroscopy, Field emission scanning electron microscopy-energy dispersive X-ray (FESEM-EDX) spectroscopy, thermogravimetric/derivative thermogravimetry (TG/DTG) and point of zero charge (pHpzc). Next, determination of the percentage of Turbidity Removal (%TR) on Egg-g-PAM, alum and egg white for coagulation/flocculation on a 0.25 g/L of kaolin suspension at pH 7 and 2 g/dL dosage. The optimum Egg-g-PAM was obtained by using 1 g of AM, 0.3 g of CAN and 2 min of irradiation time as it was able to obtain 52.1% of %GE, 185% of %WA and 95.6% of %TR. The %TR of optimum Egg-g-PAM (95.6%) was higher than that of alum (94.6%) and egg white (19.9%).